2008
DOI: 10.1016/j.apmr.2008.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Balance Factors Predict Future Falls in Community-Living Older Adults

Abstract: Objective To prospectively determine the capacity of measures of mediolateral (ML) protective stepping performance, maximum hip abduction torque, and trunk mobility, in order to predict the risk of falls among community-living older people. Design Cross-sectional study. Setting A balance and falls research laboratory. Participants Medically screened and functionally independent community-living older adult volunteers (N=51). Interventions Not applicable. Main Outcome Measures Measures included: (1) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
194
3
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(227 citation statements)
references
References 30 publications
13
194
3
17
Order By: Relevance
“…Impaired ML-balance control in standing has been identified as a common cause of falls among older adults (Robinovitch et al, 2013) and hip abductor strength is predictive of future falls (Hilliard et al, 2008). We therefore suggested that hip abductor strength might limit ML-weight-shifting performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired ML-balance control in standing has been identified as a common cause of falls among older adults (Robinovitch et al, 2013) and hip abductor strength is predictive of future falls (Hilliard et al, 2008). We therefore suggested that hip abductor strength might limit ML-weight-shifting performance.…”
Section: Discussionmentioning
confidence: 99%
“…Incorrect weight shifting is the most common cause of falling, and standing is one of the three classes of activities during which most falls in older adults occur (Robinovitch et al, 2013). Balance impairment, particularly in mediolateral (ML) direction, is suggested to be an important risk factor for such falls (Hilliard et al, 2008;Lord et al, 1999;Tinetti et al, 1988), and community-dwelling older adults are less able to actively control ML displacement of the center of mass (CoM) than young adults (Cofre Lizama et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…En el programa de estimulación motora, se realizaron ejercicios de miembros inferiores con énfasis en musculatura de cadera (abductores de cadera), ya que se ha demostrado que se encuentra fuertemente implicada en el mantenimiento del equilibrio y la marcha (Domínguez-Carrillo, Arellano-Aguilar & Leos-Zierold, 2007;Graham, Carty, Lloyd & Barret, 2015;Hilliard et al, 2008). También se trabajó musculatura de tronco mediante actividades de estabilización, giros y transferencias, ya que se han documentado mejorías del equilibrio dinámico luego de realizar este tipo de ejercicios (Granacher, Lacroix, Muehlbauer, Roettger & Gollhofer, 2013).…”
Section: Discussionunclassified
“…There is considerable evidence that many such individuals have impaired balance-recovery reactions and may be at increased risk of falls [7][8][9][10] ; hence, stabilizing-footwear could well be of benefit to this demographic. Of course, older adults having more pronounced balance impairments or disorders may well benefit the most from improved footwear, and further research is needed to examine the effects of widened footwear in such populations.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults often appear to experience difficulty in responding to lateral balance perturbation [7][8][9][10][11][12][13][14] , and a number of these difficulties have been found to predict increased risk of falling in daily life [7][8][9][10][11] . Older adults tend to be less able than younger persons to maintain upright stance without exceeding their BOS stability limits, i.e.…”
mentioning
confidence: 99%